Dissection of a truth regime: the narrowing effects on the public good of neoliberal discourse in the Virginia performance-based funding policy. Issue 2 (3rd March 2016) - Letizia, Angelo J.
Abstract : A major role of all public higher education institutions is to foster the public good. In democratic societies, the public good emphasizes the more collective activities and benefits and how resources are accessible to all in a society. Institutions of higher education create new knowledge, promote cultural tolerance, increase civic activity, and have lasting intergenerational effects among other things which all serve to enhance the collective activities of a polity. Since public higher education institutions promote the public good, and since public higher education institutions are governed by policy, educational policy becomes a crucial determiner of the public good. Moreover, policies are constructed with language or discourse. Thus, the discourse of policy, which has the power to structure the actions, speech, and thoughts of those affected by the policy, has a direct impact on the public good. In light of this importance, this paper critically examines the discourse of educational policy.